Changes in the Inflammatory Potential of Diet Over Time and Risk of Colorectal Cancer in Postmenopausal Women - Tabung, Fred K. (Am J Epidemiol, 2017)
We examined the associations between changes in dietary inflammatory potential and risk of colorectal cancer (CRC) in 87,042 postmenopausal women recruited from 1993–1998 by the Women's Health Initiative, conducted in the United States. Food frequency questionnaire data were used to compute patterns of change in dietary inflammatory index (DII) scores and cumulative average DII scores over 3 years. Cox regression models were used to estimate hazard ratios for CRC risk. After a median of 16.2 years of follow-up, 1,038 CRC cases were diagnosed. DII changes were not substantially associated with overall CRC, but proximal colon cancer risk was higher in the proinflammatory-change DII group than in the antiinflammatory-stable DII group (hazard ratio = 1.32, 95% confidence interval: 1.01, 1.74). Among nonusers of nonsteroidal antiinflammatory drugs (NSAIDs) (P(interaction) = 0.055), the proinflammatory-stable DII group was at increased risk of overall CRC and proximal colon cancer. Also among nonusers of NSAIDs, risks of overall CRC, colon cancer, and proximal colon cancer were higher in the highest quintile compared with the lowest cumulative average DII quintile (65%, 61%, and 91% higher risk, respectively). Dietary changes toward, or a history of, proinflammatory diets are associated with an elevated risk of colon cancer, particularly for proximal colon cancer and among nonusers of NSAIDs.